Household Food Security and Birth Size of Infants: Analysis of the Bangladesh Demographic and Health Survey 2011 - Chowdhury, Morseda (Curr Dev Nutr, 2018)
BACKGROUND: More than one-third of the population in Bangladesh is affected by household food insecurity in a setting where child survival and well-being are under threat. The relation between household food security and birth size of infants is an important area to explore given its explicit effect on mortality and morbidity. OBJECTIVE: Our study aims to estimate the association between household food security and birth size of infants. METHODS: For the analysis we used a nationally representative cross-sectional survey of 8753 households with a live birth between 2006 and 2011, collected under the Bangladesh Demographic and Health Survey (BDHS) 2011. We investigated the association of small birth size with the following potential explanatory variables: sex of the child; birth interval; mother's age at birth, height, body mass index (BMI), anemia status, parity, previous pregnancy loss, antenatal care visits, exposure to television, and participation in health care decisions; cooking fuel; parents' education level; region; place of residence; and wealth index using Pearson's chi-square test. We then constructed a multivariable logistic regression model of birth size on food security after controlling for all potential confounders as well as the cluster sampling design. The odds ratio (OR) was reported for each of the covariates; a P value <0.05 was interpreted as statistically significant. RESULTS: A total of 1485 (17.3%) children were reported as small at the time of birth and more than one-third of households (35.7%) experienced some degree of food insecurity. Mothers from food-insecure households had 38% higher odds of having small-size infants compared to food-secure households (adjusted OR: 1.38; 95% CI: 1.19, 1.59; P < 0.001). CONCLUSION: Household food security is one of the key factors associated with small birth size. Interventions to increase birth size should target women belonging to food-insecure households.